Recent Advances in Chemical Kinetics - Akhyar Farrukh, Muhammad (IntechOpen, 2022)
Recent Advances in Chemical Kinetics provides a comprehensive overview of several types of chemical reactions. It includes six chapters that discuss solvent catalysis, customized flow reactors, p-conjugation in kinetics, kinetics of autoxidation, molecular chameleon for cations and anions, and internal clocks of atoms.